Determinant IPO Underpricing in the Post-Pandemic Period: The Effects of Underwriter Reputation Moderation - Marselina Selie; Ahmad Shalahuddin; Anwar Azazi; Wendy; Anggraini Syahputri (Journal of Educational Management Research, 2026)
This study aims to examine the effects of firm age, proceeds, market return, and return on assets on IPO underpricing, as well as the moderating role of underwriter reputation. Grounded in signaling theory, information asymmetry theory, and behavioral finance theory, the study explains how company characteristics and market conditions influence investor perceptions and uncertainty before an initial public offering. This research employs a quantitative approach using secondary data obtained from company prospectuses and official economic sources. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA), supported by descriptive statistics, classical assumption tests, and robustness testing to address potential heteroscedasticity issues. The findings reveal that firm age has no significant effect on underpricing, whereas proceeds, market return, and return on assets significantly influence underpricing. Furthermore, underwriter reputation is only able to moderate the relationship between firm age and underpricing, while it does not moderate the relationships between proceeds, market return, return on assets, and underpricing. These findings provide empirical implications for understanding the role of company fundamentals, market conditions, and underwriter credibility in shaping IPO underpricing behavior in the post-pandemic capital market environment.